THE EFFECT OF MOTIVATION ON THE MOTOR ACTIVITIES OF STUDENTS UNDER DIFFERENT PHYSICAL EDUCATION APPROACHES - E. M. Revenko; V. A. Salnikov (Образование и наука)
Introduction. Motivation of pupils is the principal aspect in successful physical education. One of the main objectives of a physical-education teacher is to create in pupils a strong desire to consciously and voluntarily carry out regular physical exercises and develop the potential to work independently.The aim of the research was to show the influence of various approaches to the organization of sports activities on motivation leading to physical activity in young men aged 16–18.Methodology and research methods. The methodological base of the research involved a personally-oriented educational concept combining differentiated and kinesiological approaches to physical education. The research was carried out in phases using annual and longitudinal tests to evaluate students’ knowledge and skills. Levels of general intelligence were estimated using the I-S-T 2000R test as adapted by L. A. Yasyukova. Formal-dynamic characteristics of individuality were studied using the method developed by V. M. Rusalov. In order to evaluate motivation for the realization of motor activity, a specially-designed questionnaire was used. IBM SPSS Statistics 22 and Microsoft Excel software programs were employed for statistical processing of primary experimental material.Results and scientific novelty. A comparative analysis of the personal characteristics of senior school students and 1st year students (177 people) identified heterochronism in the development of standard motive and mental abilities of young people. It was observed that a lack of synchronism in the formation of separate functional systems in an organism causes a different attitude of school students to physical exercises implemented through an integrated program and standard approach without taking into account individual characteristics of young men. As compared with their peers, motivation to sport activities is initially higher among pupils with higher motor function. A formative level of general intelligence is lower due to students’ potential success when performing a wide complex of activities required by the physical culture curriculum. However, allowing free choice in sport specialization significantly increases the motivation of young people who are physically weaker but who are more intellectually developed than their peers.Practical significance. The research outcomes serve as scientific justification for the more extensive introduction of sports-oriented approach into educational institutions when organizing physical education. A sports-oriented approach is focused on preferences and interests of each student. The approach provides a free choice of the most attractive kinds of activity which gives a feeling of satisfaction and self-confidence, and consequently, enhances motivation to physical selfimprovement through visiting fitness centres and gyms which, in turn, will ensure good health in the future.